Synergistic In Vitro Antiviral Effect of Combinations of Ivermectin, Essential Oils, and 18-(Phthalimid-2-yl)ferruginol against Arboviruses and Herpesvirus (2023)
ABSTRACT: Combining antiviral drugs with different mechanisms of action can help prevent the development of resistance by attacking the infectious agent through multiple pathways. Additionally, by using faster and more economical screening methods, effective synergistic drug candidates can be rapidly identified, facilitating faster paths to clinical testing. In this work, a rapid method was standardized to identify possible synergisms from drug combinations. We analyzed the possible reduction in the antiviral effective concentration of drugs already approved by the FDA, such as ivermectin (IVM), ribavirin (RIBA), and acyclovir (ACV) against Zika virus (ZIKV), Chikungunya virus (CHIKV), and herpes virus type 2 (HHV-2). Essential oils (EOs) were also included in the study since they have been reported for more than a couple of decades to have broad-spectrum antiviral activity. We also continued studying the antiviral properties of one of our patented molecules with broad-spectrum antiviral activity, the ferruginol analog 18-(phthalimid-2-yl)ferruginol (phthFGL), which presented an IC99 of 25.6 μM for the three types of virus. In general, the combination of IVM, phthFGL, and oregano EO showed the greatest synergism potential against CHIKV, ZIKV, and HHV-2. For instance, this combination achieved reductions in the IC99 value of each component up to ~8-, ~27-, and ~12-fold for CHIKV, respectively. The ternary combination of RIBA, phthFGL, and oregano EO was slightly more efficient than the binary combination RIBA/phthFGL but much less efficient than IVM, phthFGL, and oregano EO, which indicates that IVM could contribute more to the differentiation of cell targets (for example via the inhibition of the host heterodimeric importin IMP α/β1 complex) than ribavirin. Statistical analysis showed significant differences among the combination groups tested, especially in the HHV-2 and CHIKV models, with p = 0.0098. Additionally, phthFGL showed a good pharmacokinetic profile that should encourage future optimization studies.